Transactions on computational science VI - Gavrilova, Marina L. (Lecture notes in computer science, 2009)
The LNCS journal Transactions on Computational Science reflects recent developments in the field of Computational Science, conceiving the field not as a mere ancillary science but rather as an innovative approach supporting many other scientific disciplines. The journal focuses on original high-quality research in the realm of computational science in parallel and distributed environments, encompassing the facilitating theoretical foundations and the applications of large-scale computations and massive data processing. It addresses researchers and practitioners in areas ranging from aerospace to biochemistry, from electronics to geosciences, from mathematics to software architecture, presenting verifiable computational methods, findings and solutions and enabling industrial users to apply techniques of leading-edge, large-scale, high performance computational methods. The sixth volume of the Transactions on Computational Science journal contains the thoroughly refereed best papers selected from the International Conference on Computational Science and Its Applications, ICCSA 2008. All 21 papers included in the issue have been significantly revised and extended following the event. The journal has been divided into two parts. The 11 papers in Part 1 are devoted to the theme of information systems and communications and the 10 papers in Part 2 focus on geographical analysis and geometric modeling.